Activity-Level Waste-Time Diagnosis in Corrective Maintenance Using WAM-T: Evidence from 40 Repair Events in Manufacturing Lines - Rohmad Basuki; Imam Baihaqi (Yayasan Inovasi Kemajuan Intelektual, 2026)
Corrective maintenance plays an important role in maintaining machine availability and the stability of the production process. However, maintenance performance measurement still relies heavily on macro indicators such as Overall Equipment Effectiveness (OEE), Mean Time Between Failures (MTBF), and Mean Time To Repair (MTTR). These indicators are useful for evaluating system performance, but they are not sufficient to identify which activities cause time waste during the repair process. This study aims to diagnose waste time in corrective maintenance activities using Waste Analysis Mapping–Time (WAM-T). The research data came from 40 repair events on manufacturing production lines collected through field observations, Computerized Maintenance Management System (CMMS) data, and technician interviews. Each repair activity is mapped, timed, and classified into value-added (VA), necessary non-value-added (NNVA), and non-value-added (NVA). The results showed that, out of a total of 7,055 repair minutes, VA activity accounted for 2,340 minutes (33.17%), NNVA for 4,054 minutes (57.46%), and NVA for 661 minutes (9.37%). The largest types of waste come from the Skill/Knowledge Gap (260 minutes) and the Inventory (197 minutes). These findings show that WAM-T provides more detailed visibility into the repair-time structure and the points at which waste time occurs. Thus, WAM-T can be used as a practical diagnostic tool to help maintenance management determine improvement priorities based on actual data in the field.